EEG in WNV Neuroinvasive Disease. Issue 2 (March 2019) - Parsons, Angela M.; Grill, Marie F.; Feyissa, Anteneh M.; Britton, Jeffrey; Hocker, Sara; Crepeau, Amy
Abstract : Purpose: Neuroinvasive West Nile virus (WNV) is rare, occurring in less than 1% of those infected, and may manifest as meningitis, encephalitis, and/or acute flaccid paralysis. Patients may present initially with nonspecific symptoms including fevers. Although rare, neuroinvasive WNV is associated with significant morbidity and mortality. The mainstay of treatment is supportive care. Electroencephalography (EEG) allows for identification of nonconvulsive status epilepticus and other epileptiform and nonepileptiform patterns suggestive of underlying cognitive dysfunction. Our aim was to describe specific EEG patterns observed in WNV neuroinvasive disease. Methods: A retrospective chart review was conducted. West Nile virus was confirmed with serum and/or cerebrospinal fluid markers. Patients with a history of abnormal EEG were excluded. Electroencephalography reports were classified into categories based on the presence of epileptiform activity, focal slowing, generalized periodic discharges with triphasic morphology, and frontally predominant generalized rhythmic delta activity. Results: In our cohort of 34 patients, 60% of focal EEG abnormalities were anterior-predominant, seen as epileptiform discharges, focal slowing, or frontally predominant generalized rhythmic delta activity. Nonepileptiform EEG patterns included nonspecific slowing and generalized periodic discharges with triphasic morphology. Two patients had electrographic seizures, one arising from the frontocentral head region. Conclusions: EEGs are important in the evaluation of WNV infection to rule out seizures or alternative causes of encephalopathy, and because of the risk of nonconvulsive seizures or status epilepticus in encephalitis. Although an anterior predominance of EEG abnormalities was seen in our cohort, this most likely is more correlative to encephalopathy than WNV itself. Although a specific correlative EEG pattern may not accompany all cases of WNV neuroinvasive disease, WNV should be considered as a possible etiology in patients presenting with an encephalitic or meningitic syndrome in the presence of abnormal EEG findings including encephalopathic patterns, particularly those with anterior predominant EEG changes.